Implementación del módulo de seguimiento de tutoría para trabajos de titulación en la UDLA - Sánchez Lllera, Luis Fernando (2014)
Current technology trends are helpful for the development of all types of institutions in all areas. Focusing purely on the part of education is undoubtedly the use of, existing systems on the market, covering administrative and academics. With these systems you can ensure that the student, from the comfort of your home, you can enroll and even upload your schedule The University of the Americas as one of the leading education institutions nationwide and abreast of new technological needs has ordered the development of this system which undoubtedly manage the records of tutoring titling projects in a digital manner, fast and reliable. To achieve this system has been used a agile development methodology such as SCRUM, an IDE development fully tested and outstanding in the market as Visual Studio integration features to SQL SERVER 2008 R2 version express which is free...